How different from pacemaker patients are recipients of implantable cardioverter-defibrillators with respect to psychosocial adaptation, affective disorders, and quality of life?. Issue 4 (1st April 2001) - Duru, F; Büchi, S; Klaghofer, R; Mattmann, H; Sensky, T; Buddeberg, C; Candinas, R
Abstract : OBJECTIVE: To assess differences in psychosocial adaptation, quality of life, and incidence of affective disorders between patients with pacemakers and those with implantable cardioverter-defibrillators (ICDs). DESIGN: Patients aged 40–70 years who underwent a first pectoral implantation of a pacemaker or an ICD system were studied. All subjects were asked to complete the hospital anxiety and depression scale (HAD), the short form general health survey (SF-36), and a specially designed device related questionnaire. Data analysis was performed for three patient groups: pacemaker (n = 76), ICD patients who received therapeutic shocks (n = 45), and ICD patients who did not receive shocks (n = 31). RESULTS: There were no differences between the three patient groups in HAD scores or in any of the SF-36 subscales or summary ratings. Probable depressive disorder (depression score > 10) was observed in 5.2%, 6.5%, and 6.6%, and probable anxiety disorder (anxiety score > 10) in 13.1%, 9.7%, 13.3% of the pacemaker, non-shocked ICD, and shocked ICD patients, respectively. There were no sex differences. However, patients in the shocked ICD group were more likely than those in the other groups to report limitations in their leisure activities, to perceive their device as a "life extender, " and to admit anxiety about battery depletion and technical problems. Forty per cent of shocked ICD patients would be interested in joining a support group. CONCLUSIONS: Despite having distinctly different medical histories and treatments, patients with pacemakers and ICDs responded similarly to validated tools of health status assessment. ICD patients who had received shocks perceived their device as prolonging their life and had greater anxiety about technical problems. Their endorsement of the potential benefits of a support group warrants further investigation.